Pediatric Hearing Aid Management: Challenges among Hispanic Families - Caballero, Ana; Muñoz, Karen; White, Karl; Nelson, Lauri; Domenech-Rodriguez, Melanie; Twohig, Michael (Journal of the American Academy of Audiology, 2017)
Hearing aid fitting in infancy has become more common in the United States as a result of earlier identification of hearing loss. Consistency of hearing aid use is an area of concern for young children, as well as other hearing aid management challenges parents encounter that may contribute to less-than-optimal speech and language outcomes. Research that describes parent hearing aid management experiences of Spanish-speaking Hispanic families, or the extent of their needs, is not available. To effectively support parent learning, in a culturally sensitive manner, providers may benefit from having a better understanding of the needs and challenges Hispanic families experience with hearing aid management.The purpose of the current study was to describe challenges with hearing aid management and use for children from birth to 5 yr of age, as reported by Spanish-speaking parents in the United States, and factors that may influence hearing aid use.This study used a cross-sectional survey design.Forty-two Spanish-speaking parents of children up to 5 yr of age who had been fitted with hearing aids.Responses were obtained from surveys mailed to parents through early intervention programs and audiology clinics. Descriptive statistics were used to describe frequencies and variance in responses.Forty-seven percent of the parents reported the need for help from an interpreter during audiology appointments. Even though parents received information and were taught skills by their audiologist, many wanted to receive more information. For example, 59% wanted to know how to meet other parents of children who have hearing loss, although 88% had previously received this information; 56% wanted to know how to do basic hearing aid maintenance, although 71% had previously received instruction. The two most frequently reported hearing aid use challenges were fear of losing the hearing aids, and not seeing benefit from the hearing aids. Hearing aid use during all waking hours was reported by more parents (66%) when their child had a good day than when their child had a bad day (37%); during the previous two weeks, 35% of the parents indicated their child had all good days.Hispanic parents wanted more comprehensive information, concrete resources, and emotional support from the audiologist to overcome hearing aid management challenges. Understanding parents’ perspectives, experiences, and challenges is critical for audiologists to provide appropriate support in a culturally sensitive manner and to effectively address families’ needs.
Keywords: families; hearing aids; hearing loss; Hispanic; pediatric audiology